Influence of Carbohydrates on Callus Proliferation During Somatic Embryogenesis in Pineapple [Ananas Comosus (L.) Merr. (Bromeliaceae) Var. Cayenne Smooth Cultivar CI 16] - Samuel, Kouadio Oi Kouadio; Salomé, Yapo Edwige Sopie; Oumar, Silue; Christophe, Adou Bini Yao; Hilaire, Kouakou Tanoh (European Scientific Journal, ESJ, 2018)
The improvement of pineapple (Ananas comosus var. Smooth Cayenne) by means of in vitro culture is less studied in Côte d’Ivoire despite the importance of this plant for this country’s economy. Our work consisted in highlighting nature and concentration effects of carbohydrates on the proliferation of calli in pineapple as a prelude to efficient embryogenesis. Callus proliferation was carried out from the base of pineapple vitroplants leaves. Thirty (30) explants were cultured on the tested culture medium. MS medium (micro- and macro elements of Murashige and Skoog) supplemented with vitamin Gamborg B5 was used as base medium to which were added 0.05 mg/L BAP, 3 mg/L picloram, 2 mg/L glycine, 1,000 mg/L glutamine, 100 mg/L casein hydrolyzate and 30 g/L carbohydrate. Sucrose was tested at different concentrations (20, 25, 30, 35 and 40 g/L). The results revealed that callus proliferation is strongly influenced (p ˂ 0.0001) by nature and concentration of carbohydrate. Sucrose with the highest dry matter content (61.34 mg) has a higher callogenic potential than the other studied carbohydrates. The concentration of 30 g/L sucrose significantly improved the calli proliferation in pineapple. Galactose and maltose were less favorable to proliferation.